2022
DOI: 10.1186/s12913-022-08100-4
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with the workload of health professionals in hospital at home: a systematic review

Abstract: Background Understanding the factors related to workload, could help hospital at home (HaH) managers to make decisions on the most appropriate and efficient use of the HaH services. Published studies on this topic are scarce, so we have conducted a systematic review to identify such factors according to published evidence. Methods Due to the heterogeneity of HaH models, HaH was defined as a care that provides a set of medical and nursing care and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…Acknowledging the significance of mobility during hospitalization, alongside recognizing the adverse impacts of immobility, is a crucial initial stride towards developing effective interventions promoting mobility and independence [ 35 ]. The care recipients’ health and functional status is also directly related to the HCWs' workload [ 36 ]. Patient-related factors such as older age, several diagnoses, low functional status, and being unable to self-care, are some of the identified risk factors for increased HCW workload [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acknowledging the significance of mobility during hospitalization, alongside recognizing the adverse impacts of immobility, is a crucial initial stride towards developing effective interventions promoting mobility and independence [ 35 ]. The care recipients’ health and functional status is also directly related to the HCWs' workload [ 36 ]. Patient-related factors such as older age, several diagnoses, low functional status, and being unable to self-care, are some of the identified risk factors for increased HCW workload [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The care recipients’ health and functional status is also directly related to the HCWs' workload [ 36 ]. Patient-related factors such as older age, several diagnoses, low functional status, and being unable to self-care, are some of the identified risk factors for increased HCW workload [ 36 ]. Greater functional independence and higher mobility levels in patients have shown to reduce staff levels of care [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, building strong relationships with patients and caregivers and providing high‐quality care are key factors in promoting positive experiences and improving healthcare outcomes for HaH patients. However, the workload, burden and payment for staff in the HaH care team remain significant issues, the operational deployment of staff, creating sustainable reimbursement and providing a safe practice environment should be considered and addressed when engaging staff and requiring them to have adequate competency and good job performance (Cordero‐Guevara et al, 2022; Kadakia et al, 2022; Karacaoglu & Leask, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…As proposed by Brody et al, electronic health records for tracking comprehensive personal treatment data and virtual health techniques for collecting real-time data should be further developed to meet patients' needs (Brody et al, 2019). Furthermore, to ensure patient safety and continuity of care, various technology innovations can be considered, including remote monitoring, telemedicine, point-of-care support and efficient allocation of healthcare professionals (Cordero-Guevara et al, 2022;Denecke et al, 2023). These measures can help patients receive appropriate, effective and continuous care at home, while also improving the efficiencies of involving patients, caregivers and healthcare professionals in the care delivery pathways and keeping them informed of any updates.…”
Section: The Representative Of Integrated Care In the Hah Service Fro...mentioning
confidence: 99%
“…Existing reviews of hospital@home care approaches focus on the effectiveness and costs (2), factors associated with the workload of healthcare professionals (7), or with perceptions of patients and healthcare professionals (8). A Cochrane review published in 2016 found that "admission avoidance hospital at home, with the option of transfer to hospital, may provide an effective alternative to inpatient care for a selected group of elderly patients requiring hospital admission" (2).…”
Section: Introductionmentioning
confidence: 99%